Hajj Funds Management Based on Maqāṣid Al-Sharīʿah; A Proposal for Indonesian Context - Samsudin; Aziz, Abdul; Syam, Roqiyul Ma'arif; Hasbi , M. Zidny Nafi; Prabuwono, Anton Satria (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
Indonesian hajj funds (BIPH) have the potential to support the implementation of hajj worship in an effective, efficient, transparent, and accountable manner while complying with Islamic law. However, it is said that the management turned out to be ineffective and unprofessional. This research aims to examine the management of hajj funds in detail using maqāṣid al-sharīʿah perspective to propose a breakthrough for its better management. It uses a normative juridical method through data presentation and explanation using an interdisciplinary perspective on maqāṣid al-sharīʿah. The data comes from journal articles, scientific documents, and statistical data. The research results show that in maqāṣid al-sharīʿah perspective, namely an instrument to create a balance of the Muslim way of life with Islamic legal values in social, political, economic, spiritual, and universal human aspects, the ḥifẓ māldimension urges using hajj funds for the benefit of society. Therefore, the Hajj Financial Management Agency (BPKH) should collaborate with the Ministry of Religious Affairs and other related stakeholders to manage Hajj funds optimally and efficiently while increasing trust and reducing negative public perceptions. Policies and regulations by the government are made in such a way that it can ease hajj pilgrims to carry out the worship comfortably, safely, smoothly, and spiritually enriching.